If the equation x 3 + 1 1 x 2 − 1 1 + ( x − 1 ) = 1 has the same solutions as the equation x 3 + b x 2 + c x + d . Find b + c + d .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I have edited your solution and made it presentable using L A T E X . You can click "Toggle LaTeX" option from the menu and copy this comment into your solution. I can't edit your solution personally since I'm not a moderator. :(
The equation can be simplified as,
( x + 1 ) ( x − 1 ) x ⋅ ( x + 1 ) ( x 2 − x + 1 ) = 1 ⟹ x 3 − x 2 + x = x − 1 ⟹ x 3 − x 2 + 1 = 0
On comparing with the given general equation, we have,
b = ( − 1 ) , c = 0 , d = 1 ⟹ b + c + d = 0
If b = − 1 , c = 0 , d = − 1 then b + c + d = − 2
Problem Loading...
Note Loading...
Set Loading...
The equation can be simplified as [x/((x+1)(x-1))] (x+1)(x2 – x +1) = 1. So x3 – x2 + x = x – 1, or x3 – x2 + 1 = 0. b=-1, c=0, d=-1, and b+c+d = 0